PERANCANGAN DAN IMPLEMENTASI SENSOR PARKIR PADA MOBIL MENGGUNAKAN SENSOR ULTRASONIK - Susanto, Rudy; Kristanto, Yohannes; Ridwanto, Sonny; Hisnuaji, Diptyo (CommIT (Communication and Information Technology) Journal, 2007)
A car driver often had trouble to park his car a narrow location, caused by a narrow parking area on the wane.Also, cars had often crashed the electric pillar or scratched the car on the wall while retreat. The problem was the driverdidn’t know condition behind vehicle because of limited of view. The research aimed to make a system that can easily helpdriver in parking his car, by using of ultrasonic parking sensor. The method used in sensor scheme parks is ultrasonicisensor to detect and measure car and balk distance by utilising of 851 family microcontroller as the main system. Theresult indicates that ultrasonic censor effective deep measurement was on distance of 2 cm – 30 m. It is that enoughultrasonic censor is effective to be implemented on censor parks.